The Crime Of Money Laundering (Tppu) According To Positive Law And Islamic Law And Its Implications For The Family (Study on the Analysis of Decision No. 86/Pid.B/2021/PN.Mnk of Manokwari District Court, West Papua Province) - Wa Ode Yuliana; Wa Ode Yuliana (UIN Siber Syekh Nurjati Cirebon, 2024)
Money laundering is a process carried out by a person or organization against illicit money, namely money originating from crime, to hide data and disguise the origin of the funds from the government or the competent authority. Money in the financial system, utilizing bank and non-bank services, includes stock exchanges, insurance, and foreign exchange trading so that this money can be issued from the economic system as halal money. The purpose of this study is first to examine more deeply the review of Islamic criminal law on corporate responsibility in money laundering according to Law No. Deeper into the impact and implications of money laundering crimes against families. The research method used by the author is qualitative, a normative juridical approach, which seeks to synchronize the legal provisions that apply in the legal protection of other legal norms or regulations with their relation to the application of these legal regulations in practice in the field. The type of research used is library research. The conclusions are as follows: First, Islamic law in money laundering is identified with embezzlement (ghulÃ»l). Second, accountability for money laundering is regulated in Law No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes (UU PP - TPPU). The predicate crimes of money laundering are regulated in Article 2 paragraph (1), namely: corruption, bribery, narcotics, psychotropics, labor smuggling, migrant smuggling in the banking sector, the capital market sector, the insurance sector, customs, excise, human trafficking, illegal arms trade, terrorism, kidnapping, theft, embezzlement, fraud, counterfeiting money, gambling, prostitution, in the fields of taxation, forestry, environment, maritime affairs and fisheries, and other crimes punishable by imprisonment for 4 (four) years or more. Third, the impact and implications of money laundering on families have many impacts, namely economic impacts, changes in childrenâ€™s behavior, impacts of a mother becoming the head of the household, and psychological effects.